Modelling national air quality strategy scenarios with UKIAM: uncertainties emerging from the integration of multiple spatial scales. (8th February 2011) - Oxley, Tim; ApSimon, Helen; Valiantis, Marios
For the UK's air quality strategy we assessed future scenarios involving reductions of emissions from traffic based on results from the UK integrated assessment model for national emissions integrated with European contributions from the Abatement Strategies Assessment Model. We quantify the uncertainties and assumptions relating to the percentage of primary NO2 in NOX emissions, background NOX concentrations and definition of background primary PM10 . We highlight the source apportionment of secondary inorganic aerosols and the significant 'imported' contributions to UK PM10 concentrations. It is crucial both to highlight all assumptions and uncertainties in models, and to interpret results and comparisons accordingly.